Robot-assisted thoracoscopic repair of tracheal gunshot wound - Antoine Nehme; Salman Zaheer; Alexander Leung (Trauma Case Reports)
A 23-year-old man suffered two gunshot wounds and upon arrival to the emergency room was found on imaging to have a large pneumothorax with considerable subcutaneous emphysema. Intubation and placement of bilateral chest tubes did not improve the patient's oxygenation; bronchoscopy revealed a 1 cm tracheal defect in the membranous wall 4 cm proximal to the carina. The patient underwent robot-assisted primary repair of the tracheal injury with a #3-0 PDS Stratafix barbed suture buttressed with an intercostal muscle flap. The patient was discharged in good condition on post-operative day 17, with follow-up bronchoscopy showing complete healing of the trachea.